OPTIMIZATION OF TIME REACTION AND HYDROXIDE ION CONCENTRATION ON FLAVONOID SYNTHESIS FROM BENZALDEHYDE AND ITS DERIVATIVES - Sri Handayani; Sunarto, Sunarto,; Susila Kristianingrum (Universitas Gadjah Mada, 2005)
The aim of this research is to determine the optimum time of reaction and concentration of hydroxide ion on chalcone, 4-methoxychalcone and 3,4-dimethoxychalcone synthesis. Chalcone and its derivatives were synthesized by dissolving KOH in ethanol followed by dropwise addition of acetophenone and benzaldehyde. Then, the mixture was stirred for several hours. Three benzaldehydes has been used, i.e : benzaldehyde, p-anysaldehyde and veratraldehyde. The time of reaction was varied for, 12, 18, 24, 30 and 36 hours. Furthermore, on the optimum reaction time for each benzaldehyde the hydroxyl ion concentration was varied from 5,7,9,11 and 13%(w/v). The results of this research suggested that the optimum time of chalchone synthesis was 12 hours, while, 4-methoxychalcone and 3,4-dimethoxychalcone were 30 hours. The optimum concentration of hydroxide ion of chalcone synthesis was 13% and for 4-methoxychalcone and 3,4-dimethoxychalcone were 11%.